Geochemistry of eclogite‐ and blueschist‐facies rocks from the Bantimala Complex, South Sulawesi, Indonesia: Protolith origin and tectonic setting. (21st October 2013) - Maulana, Adi; Christy, Andrew G.; Ellis, David J.; Imai, Akira; Watanabe, Koichiro
Abstract: We present the first data on bulk‐rock major and trace element compositions for a suite of eclogite‐ and blueschist‐facies rocks from the Bantimala Complex, Indonesia, with the aim of better constraining the protolith origins and nature of the subducted crust. The eclogites can be classified into two groups: glaucophane‐rich eclogite and glaucophane‐free eclogite, whereas the blueschists are divided into albite–epidote glaucophanite and quartz–glaucophane schists. SiO2 contents of the eclogites are 43.3–49.6 wt%, with Na2 O + K2 O contents 3.7–4.7 wt%. The blueschists show a wider range of compositions, with SiO2  = 40.7–63.8 wt% and Na2 O + K2 O = 2.7–4.5 wt%. Trace element data suggest that the eclogite protoliths include both enriched and normal mid‐oceanic ridge basalt (E‐MORB and N‐MORB) and also gabbroic cumulates. The blueschists show more variation in protoliths, which include N‐MORB, Oceanic Island Basalt (OIB) and Island Arc Basalt (IAB). Plots of element concentrations against the immobile Zr show considerable mobility of large ion lithophiles but not of high field‐strength elements during high‐pressure metamorphism, and indicate that the high SiO2 content of some blueschists is probably due to metasomatism by a LILE‐rich siliceous aqueous fluid. Strong correlations between K, Rb, Ba and Cs suggests that enrichment of these elements occurred by a single process. All the protoliths were subducted, metamorphosed to blueschist/eclogite‐facies and subsequently exhumed. It is noteworthy that the samples deduced to have come from thicker‐crust environments (OIB, IAB) were subducted to shallower depths (blueschist‐facies) than MORB‐derived samples, all except one of which reached eclogite‐facies conditions. The geochemical data of this study demonstrate the variety of ocean floor types that were subducted under the southeast margin of Sundaland in the late Jurassic period.